The Impact of Police Vessel Preparedness and Human Resource Competence on the Management of Theft-Related Crimes in the Waters of Batam, Riau Islands Province - Mulyana, Trisna; Nugroho, Mohammad Ali; Lelana, Jaka L (Journal of Industrial Engineering & Management Research, 2025)
The Singapore Strait is a strategic and congested shipping lane that directly impacts the increasing maritime activity and crime potential in the Batam waters, particularly theft on board ships. Limited port facilities compel vessels to anchor offshore, creating vulnerabilities that have drawn both national and international concern. Efforts by the Directorate of Water Police (Ditpolair) of the Indonesian National Police’s Air and Water Corps (Korpolairud Baharkam Polri) to address these crimes through patrols in high-risk areas continue to face challenges, especially due to aging patrol vessels and the low competency of human resources stemming from a performance-insensitive personnel development system. This study aims to analyze the influence of police vessel readiness and human resource competence on the handling of theft on board ships, as well as to evaluate relevant policies, strategies, and effective measures. The study population consists of 87 police vessel personnel assigned to the Batam waters, with the sample taken using a total sampling method. Key informants include the Head of Water Patrol Sub-Directorate, Operations Staff, and HR Staff of Korpolairud Baharkam Polri. The research uses a mixed-method approach. The findings reveal that: (1) police vessel readiness has a positive and significant effect on the handling of theft on board ships; (2) human resource competence has a positive and significant effect on the handling of such crimes; (3) both vessel readiness and HR competence simultaneously have a positive and significant effect on the handling of theft on board ships; and (4) the general policy proposed in this study emphasizes optimizing the handling of ship theft through enhanced vessel readiness and HR competence. This policy is translated into three main strategies: first, strengthening inter-agency maritime synergy through joint patrols to overcome limited assets and rising maritime crime threats; second, building logistics and maintenance facilities tailored to the geographical conditions of Batam to ensure operational continuity; and third, increasing personnel training to address technological skill gaps in facing increasingly complex maritime security challenges.